2003
DOI: 10.1081/erc-120022314
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Low Dose Nylestriol–Levonorgestrel Replacement Therapy on Bone Mineral Density in Women with Postmenopausal Osteoporosis

Abstract: These data suggested that CNT is effective, safe and convenient in treating postmenopausal osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…14 Nylestriol, a derivative of long-acting estriol and a kind of lente estrogen, was synthesized in China in 1984. 15 The estrogenic activity of nylestriol is 3 times that of quinestrol, 23 times that of estriol, and 510 times that of estriol when orally administered. 15 Nylestriol with adequate calcium and vitamin D intake could increase BMD at the lumbar spine, neck, and hip and decrease bone turnover markers in postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Nylestriol, a derivative of long-acting estriol and a kind of lente estrogen, was synthesized in China in 1984. 15 The estrogenic activity of nylestriol is 3 times that of quinestrol, 23 times that of estriol, and 510 times that of estriol when orally administered. 15 Nylestriol with adequate calcium and vitamin D intake could increase BMD at the lumbar spine, neck, and hip and decrease bone turnover markers in postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…15 The estrogenic activity of nylestriol is 3 times that of quinestrol, 23 times that of estriol, and 510 times that of estriol when orally administered. 15 Nylestriol with adequate calcium and vitamin D intake could increase BMD at the lumbar spine, neck, and hip and decrease bone turnover markers in postmenopausal women. 16 To the best of authors' knowledge, there have been no previous studies on the protective effect of the combination of simvastatin and nylestriol.…”
Section: Introductionmentioning
confidence: 99%
“…As an estrogen derivative, estriol has been showed to prevent postmenopausal bone loss (3,4). Recently our studies showed that administration of nylestriol can prevent bone loss in osteoporotic rats or postmenopausal women (5,6). Recently our studies showed that administration of nylestriol can prevent bone loss in osteoporotic rats or postmenopausal women (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…They found that bone loss was significantly prevented in total forearm in women with active treatment compared with control subjects. BMD at the lumbar spine tended to improve 61 . There was no side-effects observed on the breast by low-dose nylestriol treatment in the women 59,61 .…”
Section: Effects Of Low-dose Nylestriol In Postmenopausal Womenmentioning
confidence: 91%
“…BMD at the lumbar spine tended to improve 61 . There was no side-effects observed on the breast by low-dose nylestriol treatment in the women 59,61 .…”
Section: Effects Of Low-dose Nylestriol In Postmenopausal Womenmentioning
confidence: 91%